2022
DOI: 10.21037/atm-22-5750
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-related genes with post-transcriptional regulation mechanisms in hepatocellular carcinoma determined by bioinformatics and experimental validation

Abstract: Background: Ferroptosis is a form of iron-dependent cell death with increased free iron and massive lipid peroxidation. The discovery of ferroptosis offers insights into hepatocellular carcinoma (HCC) treatment.However, post-transcriptional regulation mechanisms of ferroptosis in HCC remain to be elucidated. The present study explored ferroptosis-related genes and their post-transcriptional regulation mechanisms in HCC.Methods: A ferroptosis score was computed in The Cancer Genome Atlas (TCGA) cohort via gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…We searched 177 articles focused on m6A and HCC, and about 35 works of literature have studied the expression characteristics, clinical prognosis, immune microenvironment, and immunotherapy of m6A in HCC through bioinformatics analysis (29,34). Some articles have further used cell lines to verify their analysis in vitro (35,36). Studies based on in vitro and in vivo experiments primarily involve patient samples and HCC cell lines (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…We searched 177 articles focused on m6A and HCC, and about 35 works of literature have studied the expression characteristics, clinical prognosis, immune microenvironment, and immunotherapy of m6A in HCC through bioinformatics analysis (29,34). Some articles have further used cell lines to verify their analysis in vitro (35,36). Studies based on in vitro and in vivo experiments primarily involve patient samples and HCC cell lines (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…hances its mRNA stability in a YTHDF1-dependent manner, with YTHDF1 inhibiting ferroptosis by upregulating FTH in lung cancer [74][75][76][77]. Other RNA methylation modifications, such as m1A and m5C, have also been reported to be involved in the post-transcriptional modification of ferroptosis-related genes [78,79]. Therefore, more RNA methylation targets that regulate ferroptosis need to be discovered in further studies to provide insights for clinical treatment (Figure 2).…”
Section: Rna Methylation Regulates Ferroptosismentioning
confidence: 99%
“…In the past three years, several studies have shown that RNA m 6 A marks are involved in the regulation of ferroptosis and thus affects the progression of diseases such as tumor growth and acute kidney injury [133,150,151] and that m 6 A modification regulators used in combination with ferroptosis-related genes can be diagnostic or prognostic markers for tumors in humans [130,[152][153][154][155]. Multiple m 6 A modification regulators have been shown to be aberrantly expressed in various types of tumors, and a prediction model comprising these regulators and ferroptosis-associated genes has been shown to effectively reflect the progression and prognosis of these tumor patients [23,[156][157][158][159]. Recently, our research revealed that compared to aortic samples without aortic dissection (non-AD), higher levels of METTL3 and METTL14 protein, but lower levels of FTO were detected in aortic samples with Stanford type A aortic dissection (TAAD) [3].…”
Section: The Rna M 6 a Modification In Ferroptosismentioning
confidence: 99%
“…Multiple m 6 A modification regulators have been shown to be aberrantly expressed in various types of tumors, and a prediction model comprising these regulators and ferroptosis-associated genes has been shown to effectively reflect the progression and prognosis of these tumor patients 23 , 156 - 159 . Recently, our research revealed that compared to aortic samples without aortic dissection (non-AD), higher levels of METTL3 and METTL14 protein, but lower levels of FTO were detected in aortic samples with Stanford type A aortic dissection (TAAD) 3 .…”
Section: The Rna M 6 a Modification In Ferroptosismentioning
confidence: 99%